Jackie ebook Public, private, secret. - Taraborrelli, J. Randy (2023)
THE INSTANT NEW YORK TIMES BESTSELLER! From the New York Times bestselling author of Jackie, Janet & Lee comes a fresh and often startling look at the life of the legendary former first lady, Jacqueline Kennedy Onassis. Based on hundreds of interviews with friends, family, and lovers over a thirty-year period—as well as previously unreleased material from the JFK Library—Kennedy historian J. Randy Taraborrelli paints an unforgettable new portrait of a woman whose flaws and contradictions only serve to make her even more iconic. "I have three lives," Jackie told a former lover, "public, private and secret." In this revealing biography, readers will become intimately familiar with all three. New insights from the book include: · Jackie's cold feet before her wedding to Jack Kennedy and her secret plan to avoid moving into the White House with him. · Jackie's plan to meet with the woman with whom her husband, Aristotle Onassis, was again having an affair, Maria Callas...and why, in the end, she decided against it. · The truth about the nude photos of Jackie which scandalized her in the 1970s...and which family member had betrayed her by selling them. · Her unusual relationship with Maurice Templesman, which was never what outsiders believed it to be. · The never-before-reported, last-ditch efforts to save Jackie's life with experimental cancer treatments, and the doctor who wouldn't risk jail time in order to treat her. Decades after her death and over sixty years after the assassination of President Kennedy, Jackie delivers the last word on one of the most famous women in the world.